Introduction of Multidisciplinary Prescribing Team Meeting in Dragon Square North Staffordshire Child and Adolescent Mental Health Services (CAMHS) as a Pilot and Analysis of Its Overall Impact, Including Waiting Times - Syed Shazia Rizvi; Bindu Poornamodan; Sadia Shafique (BJPsych Open, 2025)
Aims: Once referred to child and adolescent mental health services (CAMHS), children and young people often report long waiting times for assessment, diagnosis, and treatment (Young Minds, 2022). The COVID-19 pandemic also brought an unprecedented mental health crisis (UNICEF, 2021), increasing the burden on over-stretched CAMHS, thereby increasing the waiting time. Most research and quality improvement projects on ‘waiting lists’ focusses on how to avoid missed appointments or effectively manage booking/triage systems. This Multidisciplinary Prescribing Meeting Pilot project was initiated in an attempt to reduce the waiting times.